The prognostic value of the systemic inflammatory response in randomised clinical trials in cancer: A systematic review - Dolan, Ross D.; Laird, Barry J.A.; Horgan, Paul G.; McMillan, Donald C. (Critical reviews in oncology/hematology, 2018)
The prognostic value of the systemic inflammatory response in cancer has been well established in observational studies. This review aims to examine and rationalise the evidence for the role of systemic inflammation based prognostic scores in randomised clinical trials. An extensive literature review using targeted medical subject headings was carried out in the MEDLINE, EMBASE, and CDSR databases until January 2018. Titles were examined for relevance and after exclusions bibliographies were hand searched to identify additional trials. There were 29 trials containing data on 37,020 patients presented in full paper form and 8 trials containing data on 3805 patients presented in abstract form. Most trials were published within the last three years. Seven trials containing data on 6044 patients were published in 2015. Eight trials containing data on 4384 patients were published in 2016. Twelve trials containing data on 27,228 patients were published in 2017. The majority of trials were in advanced inoperable cancer and colorectal cancer was the most common cancer type with 11 articles containing data on 27,909 patients. The GPS/mGPS was shown to have prognostic value in randomised clinical trials in NSCLC, oesophageal cancer, pancreatic cancer, prostate cancer and breast cancer. The NLR/dNLR was shown to have prognostic value in randomised clinical trials in nasopharyngeal cancer, oesophageal cancer, pancreatic cancer, biliary cancer, prostate cancer and multiple cancer types. The prognostic value of systemic inflammation based prognostic scores has been confirmed in multiple trials and should be incorporated into future prospective randomised clinical trials.